287 A new UK reproductive care pathway for women with serious MTDNA disease - Grainne, Gorman; Robert, McFarland; Jane, Stewart; Catherine, Feeney; Mary, Herbert; Louise, Heslop; Emma, Blakeley; Robert, Taylor; Julie, Murphy; Doug, Turnbull (Journal of neurology, neurosurgery and psychiatry, 2018)
In March 2015, the UK government passed into law, an amendment to the Human Fertilisation and Embryology Act 1990 to permit ‘Mitochondrial Donation’. This provided a unique legal framework for techniques that make it possible to ‘replace’ mutated mitochondrial DNA (mtDNA) in human oocytes or zygotes. As a group, primary mtDNA diseases are the most prevalent of the inherited neurometabolic disorders, affecting up to 1 in 5000 live births and can often have devastating clinical consequences. To date, treatments focus on palliation of symptoms, while the emergence of reproductive techniques, such as Mitochondrial Donation, offers the first real opportunity to prevent the maternal transmission of some serious forms of mtDNA disease. The Human Fertilization and Embryo Authority (HFEA), the statutory regulatory authority charged with regulating human embryo research in the UK, has devised, a detailed regulatory process for Mitochondrial Donation. To ensure compliance with the HFEA regulations we describe how we have established a high quality, integrated care pathway that provides care that is available to anyone in the UK, and comprehensively involves pathways for couples seeking reproductive advice, IVF pathway for potential mothers with pathogenic mtDNA mutations, a pathway for donors and long-term follow up of children born.